Highly thermally conductive corrosion resistant coating material, method of making and heat exchanger
By combining worm-derived graphite with aluminum nitride composite filler and phenolic epoxy resin modified amine curing agent, the problem of insufficient thermal conductivity and corrosion resistance of existing heat exchanger coatings is solved, achieving efficient and simple coating construction and improving equipment performance and lifespan.
Patent Information
- Application Number
- CN202611534499.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-30
- Publication Date
- 2026-11-06
AI Technical Summary
Existing heat exchanger coatings have poor thermal conductivity and corrosion resistance, are complicated to apply and costly, and affect equipment efficiency and lifespan.
A composite thermally conductive filler made of worm graphite and aluminum nitride is used to form a continuous phonon transport network through treatment with a silane coupling agent, and a high cross-linking density network is formed with phenolic epoxy resin and modified amine curing agent to enhance the thermal conductivity and corrosion resistance of the coating.
It improves the thermal conductivity and acid and alkali corrosion resistance of the coating, simplifies the construction process, reduces costs, and extends the service life of the equipment.
Smart Images

Figure CN123042601A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of coating materials and coating preparation technology, and in particular to a high thermal conductivity and corrosion-resistant coating material, its preparation method, and a heat exchanger. Background Technology
[0002] As key equipment in energy conversion and chemical processes, heat exchangers' heat transfer efficiency and service life are highly dependent on the comprehensive performance of their surface protective coatings. Currently, widely used industrial heat exchanger protective coatings mainly include systems with epoxy resin, polyurethane, or silicone-modified resins as film-forming matrices, such as TH-847 high-temperature resistant anti-corrosion coating and TH-901 series two-component epoxy asphalt coatings.
[0003] However, existing technologies still have the following drawbacks: 1. The thermal conductivity of coatings used in heat exchangers is currently poor, which significantly reduces the heat exchange efficiency of the equipment. In addition, their corrosion resistance and chemical resistance are not ideal, making it difficult to effectively resist the erosion of strong acid and strong alkali media, which seriously affects the reliability and service life of the heat exchanger. 2. Existing heat exchanger coatings (such as TH-847) use a heat curing process, which requires dedicated heating equipment, making the construction process more complicated and significantly increasing costs. At the same time, this curing method severely restricts the convenience of on-site maintenance, greatly increasing the difficulty and time cost of maintenance.
[0004] 3. Existing heat exchanger coatings (such as TH-901) use a combination of primer and topcoat, and the film thickness of a single coat is relatively low. In order to achieve the required film thickness, multiple coats must be applied, which leads to long construction cycles and high overall costs, seriously restricting their large-scale application. Summary of the Invention
[0005] One of the objectives of this invention is to provide a high thermal conductivity and corrosion-resistant coating material to at least solve one of the technical problems existing in the prior art.
[0006] The second objective of this invention is to provide a method for preparing a high thermal conductivity and corrosion-resistant coating material.
[0007] The third objective of this invention is to provide a heat exchanger.
[0008] In order to achieve the above-mentioned objectives of the present invention, the following technical solution is adopted: In a first aspect, the present invention provides a high thermal conductivity and corrosion-resistant coating material, the main raw materials for which are prepared include: component A and component B; The raw materials for component A include phenolic epoxy resin, composite thermally conductive filler, solvent, and additives; wherein, the composite thermally conductive filler is a composite obtained by treating worm graphite and aluminum nitride with a silane coupling agent. Component B includes an amine curing agent.
[0009] Furthermore, the mesh size of the worm graphite is 100 to 800 mesh; Optionally, the aluminum nitride comprises spherical aluminum nitride; Preferably, the aluminum nitride has a particle size of less than or equal to 1 μm; Optionally, the phenolic epoxy resin includes Novolac type epoxy resin with an epoxy equivalent of 170-190 g / eq; Optionally, the silane coupling agent includes KH-560 and / or KH-550; Optionally, the amine curing agent is a modified amine curing agent with an amine value ranging from 340 to 370 mgKOH / g; Optionally, the solvent includes one or more of xylene, n-butanol, acetone, ethyl acetate, or tetrahydrofuran; Optionally, the additives include fumed silica and / or defoamers.
[0010] Furthermore, the raw materials of component A, by weight, include: 55-60 parts phenolic epoxy resin, 15-25 parts solvent, 1-3 parts fumed silica, 15-25 parts composite thermally conductive filler, and 0.1-0.5 parts defoamer; Preferably, the raw materials for preparing the composite thermally conductive filler include: 12-18 parts of worm graphite, 6-9 parts of aluminum nitride, and 2-5 parts of silane coupling agent; Preferably, the weight ratio of the worm graphite to the aluminum nitride is 1-3:1, more preferably 2:1; Preferably, component B is 49%-52% of the mass of phenolic epoxy resin, more preferably 51%.
[0011] In a second aspect, the present invention provides a method for preparing a high thermal conductivity and corrosion-resistant coating material, comprising: (a) The worm graphite was mixed with a silane coupling agent, and then aluminum nitride was added. After drying, a composite thermally conductive filler was obtained. (b) Mix the phenolic epoxy resin, solvent, and additives with the composite thermally conductive filler to obtain component A; (c) Add component B to component A, mix well, apply to the surface of a metal substrate, and cure to obtain the high thermal conductivity and anti-corrosion coating material; wherein, component B includes an amine curing agent.
[0012] Furthermore, in step (a), the amount of the silane coupling agent is 20% to 30% of the worm graphite; Optionally, the mixing in step (a) is carried out in an organic solvent; Optionally, the organic solvent includes one or more of ethanol, methanol, or isopropanol; Optionally, in step (a), the mixing includes a dispersion process, wherein the dispersion process rotates at a speed of 100. 200 rpm; Optionally, the mixing temperature of the worm graphite and the silane coupling agent is 35–45°C, and the mixing time is 0.5–1.5 h; Optionally, in step (a), the mixing time after adding aluminum nitride is 0.5 to 1.5 h.
[0013] Furthermore, the mixing includes a dispersion process, wherein the dispersion process is performed at a rotation speed of 800–1600 rpm.
[0014] Furthermore, the curing temperature is 20–30°C, and the curing time is 12–48 h; Furthermore, the application method includes one or more of spraying, scraping, or brushing.
[0015] Furthermore, the dry film thickness of the high thermal conductivity and corrosion-resistant coating material is 180–220 μm.
[0016] Thirdly, the present invention provides a heat exchanger in which at least a portion of the heat transfer surface is provided with the high thermal conductivity and anti-corrosion coating material described above or the high thermal conductivity and anti-corrosion coating material prepared by the preparation method described above.
[0017] Compared with the prior art, the present invention has the following beneficial effects: The high thermal conductivity and corrosion-resistant coating material provided by this invention uses worm graphite and aluminum nitride as synergistic thermally conductive fillers, and achieves their composite with the help of a silane coupling agent. This allows aluminum nitride particles to be directionally embedded in the porous structure of worm graphite, thereby constructing a continuous and interconnected phonon transport pathway in the cured coating. At the same time, aluminum nitride fills the pores of worm graphite, forming a physical barrier, thereby sealing or blocking the transport channels of corrosive media in worm graphite. On this basis, the high cross-linking density network formed by the reaction of phenolic epoxy resin and amine curing agent not only enhances the structural stability of this thermally conductive pathway, but also simultaneously improves the coating's physical barrier ability and chemical inertness against corrosive media such as strong acids and strong alkalis. Attached Figure Description
[0018] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.
[0019] Figure 1 This is a schematic diagram of the composite thermally conductive filler structure and phonon transport network.
[0020] Figure 2 These are photographs of the acid resistance tests of Example 1 and Comparative Examples 4 and 5.
[0021] Figure 3 These are thermal conductivity test samples for Example 1 and Comparative Examples 1, 2, and 3. Detailed Implementation
[0022] Unless otherwise defined herein, the scientific and technical terms used in conjunction with this invention shall have the meanings commonly understood by one of ordinary skill in the art. The meaning and scope of terms shall be clear; however, in any case of potential ambiguity, the definitions provided herein shall prevail over any dictionary or foreign definitions. In this application, unless otherwise stated, the use of "or" means "and / or". Furthermore, the use of the term "comprising" and other forms is non-limiting.
[0023] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0024] The first aspect of this invention provides a high thermal conductivity and corrosion-resistant coating material, the main raw materials for which are prepared include: component A and component B.
[0025] The raw materials of component A include phenolic epoxy resin, composite thermally conductive filler, solvent and additives; the composite thermally conductive filler is a composite obtained by treating worm graphite and aluminum nitride with a silane coupling agent, and the aluminum nitride is preferably spherical aluminum nitride.
[0026] The high thermal conductivity and corrosion-resistant coating material provided by this invention is specifically a high thermal conductivity and corrosion-resistant heat exchanger coating. It uses inexpensive worm-shaped graphite and spherical aluminum nitride (AlN) as a composite thermally conductive filler. After modification with a silane coupling agent, spherical AlN is directionally filled into the loose, porous structure of the worm-shaped graphite using chemical composite technology. This structure effectively suppresses interfacial thermal resistance and forms a continuous and efficient phonon transport network, thus endowing the material with high thermal conductivity. Simultaneously, the aluminum nitride filling the pores of the worm-shaped graphite forms a physical barrier, thereby sealing or blocking the transport channels of corrosive media in the worm-shaped graphite, improving the acid resistance and salt spray resistance of the thermally conductive and corrosion-resistant coating.
[0027] like Figure 1As shown in the figure, the porous structure of worm graphite is modified with a silane coupling agent, and spherical AlN is oriented to fill the pores, forming a continuous phonon transport channel with low interfacial thermal resistance.
[0028] Component B is an amine curing agent, which is a modified amine curing agent with an amine value ranging from 340 to 370 mg KOH / g.
[0029] In some preferred embodiments, the phenolic epoxy resin includes a Novolac type epoxy resin with an epoxy equivalent of 170-190 (g / eq).
[0030] The phenolic epoxy resin used in this invention is preferably a high-functionality phenolic epoxy resin. Because of the multiple epoxy groups distributed on its molecular chain, the high-functionality phenolic epoxy resin can trigger a multi-point cross-linking reaction at room temperature under the action of a modified amine curing agent, forming a cross-linking structure with a three-dimensional network density that is significantly higher than that of the difunctional epoxy system. This high-density network not only significantly reduces the free volume of the coating and strengthens the physical barrier against corrosive media, but also fully anchors the stable polycyclic aromatic hydrocarbon skeleton in the resin backbone to rigid cross-linking points, thereby synergistically improving its chemical bond stability and structural durability under strong acid and strong alkali environments.
[0031] The high thermal conductivity and corrosion-resistant coating material provided by this invention uses high-functionality phenolic epoxy resin and modified amine curing agent. It retains the characteristics of ordinary phenolic epoxy system such as room temperature curing, high crosslinking density and excellent temperature and chemical resistance, while also having the unique advantage of long-term resistance to strong acids and alkalis, thereby effectively improving the reliability and service life of heat exchangers.
[0032] Furthermore, this thermally conductive coating exhibits excellent application performance and wide applicability, allowing for flexible application methods such as air spraying, high-pressure airless spraying, or manual brushing to meet the coating requirements of irregularly shaped structures such as heat exchanger tube bundles and fins. Its single-coat, room-temperature curing characteristics ensure both application efficiency and quality stability, while effectively extending the service life of heat exchangers and reducing maintenance frequency, making it a highly competitive protective coating solution for high-temperature corrosive conditions.
[0033] In an optional embodiment, the worm graphite has a mesh size of 100 to 800 mesh, preferably 300 mesh.
[0034] In an optional embodiment, the aluminum nitride has a particle size of less than or equal to 1 μm, preferably 0.5-1 μm.
[0035] In an optional embodiment, the silane coupling agent includes KH-560 and / or KH-550.
[0036] In an optional embodiment, the solvent includes one or more of xylene, n-butanol, acetone, ethyl acetate, or tetrahydrofuran.
[0037] In an optional embodiment, the additives include fumed silica and / or defoamers. Fumed silica, as a thixotropic additive, can improve the suspension stability of composite thermally conductive fillers in high-solids-content systems and inhibit their sedimentation during storage and construction; defoamers are used to eliminate microbubbles trapped during mixing and dispersion, ensuring the density and continuity of the coating structure after curing.
[0038] In some preferred embodiments, the defoamer is selected from one or more of mineral oil-based defoamers, silicone-polyether copolymer-based defoamers, and polyacrylate-based defoamers.
[0039] Specifically, regarding the range of raw material weight parts for component A: The raw materials for component A, by weight, include: 55 to 60 parts of phenolic epoxy resin, for example, 55 parts, 56 parts, 57 parts, 58 parts, 59 parts, 60 parts, etc.; 15 to 25 parts solvent, for example, 15 parts, 20 parts, 25 parts, etc.; 1 to 3 parts of fumed silica, for example, 1 part, 2 parts, 3 parts, etc.; 15-25 parts of thermally conductive filler; 0.1 to 0.5 parts of defoamer, for example, 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, etc.
[0040] Preferably, the raw materials for preparing the composite thermally conductive filler include: 12 to 18 parts of worm graphite, for example, 12, 13, 14, 15, 16, 17, 18, etc.; 6 to 9 parts of aluminum nitride, for example, 6, 7, 8, 9, etc.; and 2 to 5 parts of silane coupling agent, for example, 2, 3, 4, 5, etc.
[0041] Preferably, the weight ratio of the worm graphite to the aluminum nitride is 1-3:1, and more preferably 2:1.
[0042] In some preferred embodiments, the B component is 49%-52% of the mass of the phenolic epoxy resin in the A component, more preferably 51%.
[0043] A second aspect of the present invention provides a method for preparing a high thermal conductivity and corrosion-resistant coating material, comprising: (a) The worm graphite was mixed with a silane coupling agent, and then aluminum nitride was added. After drying, a composite thermally conductive filler was obtained. (b) Mix the phenolic epoxy resin, solvent, and additives with the composite thermally conductive filler to obtain component A; (c) Add component B to component A, mix well, apply to the surface of a metal substrate, and cure to obtain the high thermal conductivity and anti-corrosion coating material; wherein, component B includes an amine curing agent.
[0044] The method for preparing a high thermal conductivity and corrosion-resistant coating material provided by this invention achieves the directional integration of worm graphite and aluminum nitride in steps, ensuring that the composite thermally conductive filler forms a spatially continuous phonon transport framework in the resin matrix. At the same time, aluminum nitride fills the pores of the worm graphite, forming a physical barrier, thereby sealing or blocking the transport channels of corrosive media in the worm graphite and improving the acid resistance and weather resistance of the thermally conductive and corrosion-resistant coating. The crosslinking reaction of phenolic epoxy resin and modified amine curing agent makes the framework stably covered and anchored by a high-density network, resulting in a functional coating with both high thermal conductivity and strong adaptability to corrosive media.
[0045] In some preferred embodiments, in step (a), the amount of the silane coupling agent is 20% to 30% of the worm graphite, for example, it can be 20%, 25%, 30%, etc.
[0046] In an optional embodiment, the mixing in step (a) is carried out in an organic solvent, and the amount of organic solvent used is preferably 85% to 90% of the mixed solution in step (a). The organic solvent includes one or more of ethanol, methanol, or isopropanol.
[0047] In an optional implementation, in step (a), the mixing includes a dispersion process at a rotation speed of 100. 200 rpm, for example, could be 100 rpm, 150 rpm, 200 rpm, etc.
[0048] In an optional embodiment, the mixing temperature of the worm graphite and the silane coupling agent is 35-45°C, for example, 35°C, 40°C, 45°C, etc., and the mixing time is 0.5-1.5 h, for example, 0.5 h, 1 h, 1.5 h, etc.
[0049] In an optional implementation, in step (a), the mixing time after adding aluminum nitride is 0.5 to 1.5 h, for example, 0.5 h, 1 h, 1.5 h, etc.
[0050] In an optional implementation, in step (b), the mixing includes a dispersion process, wherein the dispersion process is performed at a speed of 800 to 1600 rpm, for example, 800 rpm, 1000 rpm, 1200 rpm, 1400 rpm, 1600 rpm, etc.
[0051] In an optional embodiment, the curing temperature is 20-30°C, for example, 20°C, 25°C, 30°C, etc., and the curing time is 12-48 h, for example, 12 h, 24 h, 48 h, etc.
[0052] In an optional implementation, the application method includes one or more of spraying, scraping, or brushing.
[0053] In an optional embodiment, the wet film thickness of the high thermal conductivity anti-corrosion coating material (specifically, the high thermal conductivity anti-corrosion heat exchanger coating) is 250–350 μm, for example, it can be 250 μm, 300 μm, 350 μm, etc.; the dry film thickness of the high thermal conductivity anti-corrosion coating material (specifically, the high thermal conductivity anti-corrosion heat exchanger coating) is 180–220 μm.
[0054] A third aspect of the present invention provides a heat exchanger in which at least a portion of the heat transfer surface is provided with a high thermal conductivity and corrosion-resistant coating material as described in the first aspect or a high thermal conductivity and corrosion-resistant coating material prepared by the preparation method described in the second aspect.
[0055] The present invention will be further illustrated by the following examples. Unless otherwise specified, the materials in the examples are prepared according to existing methods or purchased directly from the market.
[0056] Example 1 This embodiment provides a high thermal conductivity and corrosion-resistant coating material, the preparation process of which is as follows: Step 1: Add 200 g of anhydrous ethanol and 15 g of worm-shaped graphite (300 mesh) to a reaction vessel, heat to 40°C in a water bath at 200 rpm, add 3.75 g of KH-560, and stir mechanically for 1 h. Then add 7.5 g of spherical AlN (1 μm particle size) and disperse for 1 h. Finally, filter, wash three times with anhydrous ethanol solution, and then dry at 60°C for 16 h to obtain the worm-shaped graphite / AlN microsphere composite filler.
[0057] Step 2: Add 20.2 g of xylene and 57 g of phenolic epoxy resin (Guodu Chemical model: YDPN-638, epoxy equivalent 180.1 g / eq) to a 400 ml container. Adjust the stirring speed to 400 rpm and stir for 10 min. Then add 0.4 g of defoamer BYK-065 and 2 g of fumed silica, and disperse at 1400 rpm using a high-speed disperser for 30 min. Weigh 20.4 g of the worm-shaped graphite / AlN microsphere filler prepared above and continue dispersing for 20 min to obtain the coating.
[0058] Step 3: Weigh 60 g of the above coating and add modified amine curing agent (Guodu Chemical model: XB-810, amine value 358mgKOH / g). The amount of the modified amine curing agent is 51% of the mass of the phenolic epoxy resin. Stir well.
[0059] The coating was sprayed onto a sandblasted Q235 steel plate (150 mm × 75 mm × 3 mm) with air spraying. The wet film thickness was controlled so that the coating was cured at 25°C to form a dry film thickness of 200 μm, which was then prepared for salt spray test and acid resistance test.
[0060] The coating was applied to the plastic film using a scraper to form a paint film. The wet film thickness was controlled so that the coating was cured at 25°C to form a dry film thickness of 750 μm. The paint film was then peeled off the plastic film and cut into 10 mm × 10 mm sheets for use in thermal conductivity testing.
[0061] Example 2 This embodiment provides a high thermal conductivity and corrosion-resistant coating material, which differs from Embodiment 1 in that the amount of raw materials is changed, as shown in Table 1, and the amount of worm graphite / AlN microsphere filler is adjusted to 17.5g. The rest is the same as in Example 1.
[0062] Example 3 This embodiment provides a high thermal conductivity and corrosion-resistant coating material, which differs from Embodiment 1 in that the amount of raw materials is changed, as shown in Table 1, and the amount of worm graphite / AlN microsphere filler is adjusted to 25g. The rest is the same as in Example 1.
[0063] Example 4 This embodiment provides a high thermal conductivity and corrosion-resistant coating material, which differs from Embodiment 1 in that: in step 1, the material is heated to 45°C in a water bath, a silane coupling agent is added, and the mixture is mechanically stirred for 0.5 h. Spherical AlN is then added and dispersed for 1.5 h. The rest is the same as in Example 1.
[0064] Example 5 This embodiment provides a high thermal conductivity and corrosion-resistant coating material, which differs from Embodiment 1 in that: in step 1, the material is heated to 35°C in a water bath, a silane coupling agent is added, and the mixture is mechanically stirred for 1.5 h, followed by the addition of spherical AlN and dispersion for 0.5 h. The rest is the same as in Example 1.
[0065] Example 6 This embodiment provides a high thermal conductivity and corrosion-resistant coating material. The difference from Embodiment 1 is that the amount of raw materials has changed, and the amount of silane coupling agent has been adjusted to 1g, as shown in Table 1. The rest is the same as in Embodiment 1.
[0066] Example 7 This embodiment provides a high thermal conductivity and corrosion-resistant coating material. The difference from Embodiment 1 is that the amount of raw materials has changed, and the amount of silane coupling agent has been adjusted to 6g, as shown in Table 1. The rest is the same as in Embodiment 1.
[0067] Example 8 This embodiment provides a high thermal conductivity and corrosion-resistant coating material. The difference from Embodiment 1 is that the amount of raw materials used has changed, as shown in Table 1. The rest is the same as Embodiment 1.
[0068] Example 9 This embodiment provides a high thermal conductivity and corrosion-resistant coating material. The difference from Embodiment 1 is that the amount of raw materials used has changed, as shown in Table 1. The rest is the same as Embodiment 1.
[0069] Comparative Example 1 This comparative example provides a coating that differs from Example 1 in that: Cancel step 1; In step 2, 20.2 g of xylene and 57 g of phenolic epoxy resin (Guodu Chemical model: YDPN-638, oxygen equivalent 180.1 g / eq) were added to a 400 ml container. The stirring speed was adjusted to 400 rpm and stirred for 10 min. Then, 0.4 g of defoamer BYK-065 and 2 g of fumed silica were added, and the mixture was dispersed in a high-speed disperser at 1400 rpm for 30 min. 18 g of worm graphite (300 mesh) was added, and dispersion was continued for 20 min to obtain the coating. The amount of curing agent (Guodu Chemical model: XB-810, amine value 358 mgKOH / g) was 51% of the mass of the phenolic epoxy resin. The subsequent construction method was the same as that in step 3 of Example 1.
[0070] Comparative Example 2 This comparative example provides a coating that differs from Comparative Example 1 in that the filler is adjusted to 34.29 g of Al2O3 (particle size of 10 μm), and the amount of curing agent is 51% of the mass of phenolic epoxy resin; the rest is the same as Comparative Example 1.
[0071] Comparative Example 3 This comparative example provides a coating that differs from Comparative Example 1 in that the filler is adjusted to 27.94 g of spherical AlN (particle size of 1 μm), and the amount of curing agent is 51% of the mass of phenolic epoxy resin; the rest is the same as Comparative Example 1.
[0072] Comparative Example 4 This comparative example provides a coating that differs from Example 1 in that the curing agent is replaced with a polyamide curing agent (G-640), and the amount used is 55.5% of the mass of the phenolic epoxy resin; the rest is the same as in Example 1.
[0073] Comparative Example 5 This comparative example provides a coating that differs from Example 1 in that: the phenolic epoxy (YDPN-638) is replaced with bisphenol A epoxy resin (YD-128), the curing agent is G-640, and the amount used is 58.8% of the mass of YD-128; the rest is the same as in Example 1.
[0074] Comparative Example 6 This comparative example provides a coating that differs from Example 1 in that: Cancel step 1; In step 2, 20.2 g of xylene and 57 g of phenolic epoxy resin (Guodu Chemical model: YDPN-638, oxygen equivalent 180.1 g / eq) were added to a 400 ml container. The stirring speed was adjusted to 400 rpm and stirred for 10 min. Then, 0.4 g of defoamer BYK-065 and 2 g of fumed silica were added, and the mixture was dispersed in a high-speed disperser at 1400 rpm for 30 min. 13.6 g of worm-shaped graphite (300 mesh) and 6.8 g of spherical AlN (particle size 1 μm) were added, and dispersion was continued for 20 min to obtain the coating. The amount of curing agent (Guodu Chemical model: XB-810, amine value 358 mgKOH / g) was 51% of the mass of the phenolic epoxy resin. The subsequent construction method was the same as that in step 3 of Example 1.
[0075] It should be noted that the amount of thermally conductive filler added in the above comparative examples is the same as the amount used in Example 1, with equal volume replacement.
[0076] Table 1
[0077] Test case The coatings prepared using the above-described embodiments and comparative examples were tested.
[0078] Test method: The thermal conductivity of the coating was tested using a laser thermal conductivity meter. According to GB / T 1771 Salt spray test conducted in 2007; According to GB / T 9274 Acid resistance tests were conducted in 1998.
[0079] The test results are shown in Table 2.
[0080] Table 2
[0081] As shown in Table 2, Examples 1, 4, and 5 exhibit excellent thermal conductivity, with thermal conductivity measured by the laser method all exceeding 1.0 W·m⁻¹·K. -1 Furthermore, it exhibits excellent resistance to environmental aging: after 2000 hours of neutral salt spray testing (NSS), no blistering or peeling was observed on the sample surface; after immersion in a more stringent 20% sulfuric acid solution at 60°C for 3 months, the coating remained intact without blistering or penetration of corrosive media. This demonstrates that the coating provided by this invention possesses high thermal conductivity, excellent corrosion resistance, and acid resistance.
[0082] Comparative analysis was conducted on Examples 1, 2, and 3. Test results showed that the amount of thermally conductive filler significantly affected the thermal conductivity. In Example 2, the amount of thermally conductive filler was 17.5 g, slightly lower than in Example 1, but still significantly better than Comparative Example 1 and the single filler system, indicating that an effective phonon pathway had been initially constructed with 17.5 g of composite filler. In Example 3, increasing the amount of thermally conductive filler to 25 g increased the thixotropy of the coating, leading to high scraping resistance, easy clogging of the spray gun, and the generation of bubbles and pinholes in roller coating. This had a certain impact on coating uniformity and construction efficiency. Simultaneously, the large specific surface area of the filler prevented the resin matrix from completely wetting and displacing all air from the microscopic gaps, resulting in a decrease in thermal conductivity compared to Example 1.
[0083] Comparative analysis was conducted on Examples 1, 6, and 7. The test results show that the amount of silane coupling agent added has a non-linear effect on the improvement of thermal conductivity. In Example 6, the amount of coupling agent used was only 1 g, and the thermal conductivity of the prepared sample was only 0.86 W·m. -1 ·K -1 This indicates that insufficient coupling agent cannot completely coat the surface of the inorganic filler, resulting in high interfacial bonding energy and increased defects between the inorganic filler and the worm graphite matrix. Phonon scattering is intensified at the interface, making it impossible to effectively overlap and form a through-type thermally conductive network. In Example 7, the amount of coupling agent was increased to 6 g. Excessive coupling agent produces bridging or adhesive effects between the layered structures of the worm graphite, exacerbating the physical aggregation of the graphite sheets. At the same time, the excessively thick organic coating layer itself has extremely low thermal conductivity, becoming an additional thermal resistance barrier, which in turn damages the filler dispersion and thermal conductivity pathways, leading to a decrease in thermal conductivity.
[0084] Comparative analysis was conducted on Examples 1, 8, and 9. Test results showed that the optimal ratio of worm-like graphite to AlN was 2:1. This indicates that when the AlN ratio is too high, the rigid AlN particles are overfilled, disrupting the continuous three-dimensional network structure of the worm-like graphite. Furthermore, the solid-solid point contact between inorganic particles increases dramatically, leading to a sharp accumulation of contact thermal resistance. When the worm-like graphite ratio is too high, the number of AlN bridging nodes is insufficient, resulting in a lack of rigid support and tight connection between graphite sheets, causing local interruptions in heat conduction pathways. Moreover, excessive flexible graphite sheets are prone to stacking misalignment under shear force, and the thermal conductivity shows a marginal decrease or even decline trend with increasing ratio.
[0085] Figure 3 To test the thermal conductivity of the samples from Example 1 and Comparative Examples 1, 2, and 3, laser scattering was used to determine the thermal conductivity of the samples. Analysis of the results showed that, compared to using worm-like graphite, alumina, or AlN fillers alone, the worm-like graphite / AlN composite thermally conductive filler used in Example 1 exhibited a significant synergistic effect. The three-dimensional porous network of worm-like graphite provided a framework-filled spatial structure for the AlN microspheres. The AlN particles embedded within the worm-like graphite increased solid-solid contact points and reduced the porosity caused by the shape or size of individual fillers. The synthesized worm-like graphite / AlN composite thermally conductive filler exhibited significantly superior thermal conductivity compared to the single thermally conductive fillers used.
[0086] A comparative analysis was conducted between Example 1 and Comparative Examples 4 and 5. The test results showed that Example 1 used a phenolic epoxy resin and modified amine curing system, while Comparative Examples 4 and 5 used a common polyamide / bisphenol A epoxy system. The significant difference in acid resistance between the two examples stemmed from differences in the cured crosslinking structure and the stability of chemical bonds. Linear phenolic epoxy resin possesses a high crosslinking density and a benzene ring backbone, forming a dense three-dimensional network after curing, which effectively blocks acid molecules (H... + Cl - (etc.) Penetration; at the same time, the polar groups introduced by the modified amine curing agent can form chemical bonds with the filler surface, further blocking the micropore channels. The degree of cross-linking of ordinary bisphenol A epoxy / polyamide system is relatively low and the content of ester bonds is high. It is prone to hydrolysis or swelling in acidic environments, resulting in coating interface peeling and rapid penetration of corrosive media along the filler-resin interface, thus exhibiting very poor acid resistance.
[0087] A comparative analysis was conducted between Example 1 and Comparative Examples 1 and 6. Example 1, using worm-shaped graphite / AlN filler treated with a silane coupling agent, exhibited significantly better thermal conductivity and corrosion resistance than the worm-shaped graphite system used alone in Comparative Example 1 and the simple physical blending system in Comparative Example 6. In Comparative Example 1, although worm-shaped graphite possesses excellent thermal conductivity potential, its porous structure provides a transport channel for corrosive media such as hydrogen ions to enter the substrate and reduces the tortuosity of the diffusion path, thereby shortening the effective penetration path of the corrosive media and leading to a decrease in the system's acid resistance and salt spray resistance. In Comparative Example 6, although both worm-shaped graphite and spherical AlN are high thermal conductivity fillers, they were not bridged by a coupling agent and were only macroscopically mixed by mechanical stirring. The interfacial bonding between the two phases was weak, and phase separation and disordered accumulation easily occurred in the resin matrix. The AlN particles could not be directionally embedded into the porous structure of the worm-shaped graphite, failing to form a continuous, low-interfacial-thermal-resistance phonon transport network, resulting in significantly inferior thermal conductivity compared to Example 1.
[0088] also, Figure 2 The surface states of Example 1, Comparative Examples 4 and 5 are shown in an acid-resistant environment. Figure 2 It can be seen that after immersion in acidic medium, the coating surface of Example 1 remained dense and smooth, without blistering, peeling, or discoloration; the coating surfaces of Comparative Examples 4 and 5 both showed obvious blistering, accompanied by varying degrees of gloss loss; among them, the blistering phenomenon of Comparative Example 5 was the most significant, with a large number of bubbles densely distributed on the surface. The above comparison shows that the combination of phenolic epoxy resin and modified amine curing agent can form a high cross-linking density network, which not only improves the density and chemical inertness of the coating, but also strengthens the interfacial adhesion of the thermally conductive filler, thereby significantly enhancing the long-term protective ability of the coating in acidic environments.
[0089] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A high thermal conductivity and corrosion-resistant coating material, characterized in that, Its main raw materials include: component A and component B; The raw materials for component A include phenolic epoxy resin, composite thermally conductive filler, solvent, and additives; wherein, the composite thermally conductive filler is a composite obtained by treating worm graphite and aluminum nitride with a silane coupling agent. Component B includes an amine curing agent.
2. The high thermal conductivity and corrosion-resistant coating material according to claim 1, characterized in that, The mesh size of the worm graphite is 100-800 mesh; Optionally, the aluminum nitride comprises spherical aluminum nitride; Preferably, the aluminum nitride has a particle size of less than or equal to 1 μm; Optionally, the phenolic epoxy resin includes Novolac type epoxy resin with an epoxy equivalent of 170-190 g / eq; Optionally, the silane coupling agent includes KH-560 and / or KH-550; Optionally, the amine curing agent is a modified amine curing agent with an amine value ranging from 340 to 370 mgKOH / g; Optionally, the solvent includes one or more of xylene, n-butanol, acetone, ethyl acetate, or tetrahydrofuran; Optionally, the additives include fumed silica and / or defoamers.
3. The high thermal conductivity and corrosion-resistant coating material according to claim 2, characterized in that, The raw materials of component A, by weight, include: 55-60 parts phenolic epoxy resin, 15-25 parts solvent, 1-3 parts fumed silica, 15-25 parts composite thermally conductive filler, and 0.1-0.5 parts defoamer. Preferably, the raw materials for preparing the composite thermally conductive filler include: 12-18 parts of worm graphite, 6-9 parts of aluminum nitride, and 2-5 parts of silane coupling agent; Preferably, the weight ratio of the worm graphite to the aluminum nitride is 1-3:1, more preferably 2:1; Preferably, component B is 49%-52% of the mass of phenolic epoxy resin, more preferably 51%.
4. The method for preparing the high thermal conductivity and corrosion-resistant coating material according to any one of claims 1-3, characterized in that, include: (a) The worm graphite was mixed with a silane coupling agent, and then aluminum nitride was added. After drying, a composite thermally conductive filler was obtained. (b) Mix the phenolic epoxy resin, solvent, and additives with the composite thermally conductive filler to obtain component A; (c) Add component B to component A, mix well, apply to the surface of a metal substrate, and cure to obtain the high thermal conductivity and anti-corrosion coating material; wherein, component B includes an amine curing agent.
5. The preparation method according to claim 4, characterized in that, In step (a), the amount of silane coupling agent used is 20% to 30% of the worm graphite; Optionally, the mixing in step (a) is carried out in an organic solvent; Optionally, the organic solvent includes one or more of ethanol, methanol, or isopropanol; Optionally, in step (a), the mixing includes a dispersion process, wherein the dispersion process rotates at a speed of 100. 200 rpm; Optionally, the mixing temperature of the worm graphite and the silane coupling agent is 35–45°C, and the mixing time is 0.5–1.5 h; Optionally, in step (a), the mixing time after adding aluminum nitride is 0.5 to 1.5 h.
6. The preparation method according to claim 4, characterized in that, In step (b), the mixing includes a dispersion process at a rotation speed of 800–1600 rpm.
7. The preparation method according to claim 4, characterized in that, The curing temperature is 20–30°C, and the curing time is 12–48 h.
8. The preparation method according to claim 4, characterized in that, The application method includes one or more of spraying, scraping, or brushing.
9. The preparation method according to claim 4, characterized in that, The dry film thickness of the high thermal conductivity and anti-corrosion coating material is 180–220 μm.
10. A heat exchanger, characterized in that, At least a portion of the heat transfer surface is provided with a high thermal conductivity and corrosion-resistant coating material as described in any one of claims 1-3 or a high thermal conductivity and corrosion-resistant coating material prepared by the preparation method described in any one of claims 4-9.
